STRUKTUR WACANA IKLAN MEDIA CETAK KAJIAN STUKTUR VAN DJIK - Mulyawan, I Wayan (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 17 (2010): March 2010, 2010)
Discourse of advertisements, especially in printed ads, has shown the development of an extraordinary language phenomenon. A copywriter is able to exploit the language to be used as the media of communicative ads, which is very interesting and persuading. This exploitation of language, especially the mixture of verbal and non-verbal signs, makes discourse of ads an interesting subject to explore and analyze. To study the exploitation of the language in the discourse of ads, there are three main points to learn as proposed by Van Dijk; They are : superstructure, micro structure, and macro structure of the ads. The study shows that, superstructure of an ads should has body copy which shows persuasiveness; in micro structure, the exploitation of verbal aspect intensely applied the grammatical roles of ellipsis, substitution and references; meanwhile in macro structure, an ads could shows remarkable persuasiveness through verbal and visual aspect